The Space Robotics Lab 2016-2023. - Pérez-del-Pulgar-Mancebo, Carlos Jesús (My University, 2023)
This presentation introduces the Space Robotics Lab at the University of Malaga, which was presented at ICRA2023 workshop.
Keywords: Robótica - Estudio y enseñanza superior; Robotics; Space; Laboratory